DEVELOPMENT OF PAPUA LOCAL WISDOM BASED MATHEMATICS MODULE TO IMPROVE LEARNING OUTCOMES IN GEOMETRY TRANSFORMATION MATERIALS - Cornely Filimdity (Jurnal Ilmu Pendidikan Indonesia, 2021)
This research is a development research (Research & Development) which aims to: determine the feasibility of developing a mathematics module based on Papuan local wisdom in class XI students of SMA Negeri 9 Raja Ampat. The development of this module, the researcher refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) with an experimental design using a pre test post test one group design, which uses one research class with a sample of 24 students. The module is developed through 5 stages, namely curriculum and needs analysis, module design, module development, testing the module on a small and wide scale and evaluating the module. Material validation results obtained 92.05% and media validation results with 89.18% meaning that the module is suitable for use in learning by revising. Data analysis results using SPSS 26 for a small scale there are 15 valid questionnaire questions from 20 questions, and the average percentage is 90.21, the reliability value is 0.935, this shows that the questionnaire instrument has a very high level of reliability. The large-scale test for students in class XI is 91.41%, meaning that this module is feasible and effective in improving learning outcomes in geometry transformation material. The n-Gain in the four lesson plans is 0.71, which means that the use of mathematics modules based on Papuan local wisdom is very effective in learning.